(untitled) (Our Nature, 2025)
Gastrointestinal (GI) parasites pose a crucial health risk to non-human primates (NHPs), particularly in areas with frequent human-wildlife interaction. This study assessed the prevalence and diversity of GI parasites in free-ranging Macaca mulatta (Rhesus macaque) and Semnopithecus hector (Hanuman langur) in Dharan, eastern Nepal, in the year 2024. The collected fecal samples (n=89) were examined using direct wet mount and flotation techniques. Overall, the parasitic prevalence (74.15%), with helminths (65.15%), was found to be more than protozoans (33.70%). Notably, Trichuris sp. was the most prevalent parasite (48.63%). In addition, M. mulatta showed higher parasite diversity (Shannon H’=1.96) and protozoan prevalence (43.63%) compared to S. hector (H’=1.72; 17.64%), likely due to their synanthropic behavior. Moreover, the co-infections were found to be more frequent, particularly in macaques. These results highlight the zoonotic risks associated with gastrointestinal parasites and underscore the role of human activities, such as improper waste disposal and habitat disturbance, in facilitating parasite transmission. This calls for targeted habitat management strategies, improved waste management practices, and public health interventions to reduce disease risks in urban areas where human and primate populations coexist.